Functional Analysis of the Chaperone-Usher Fimbrial Gene Clusters of Salmonella enterica serovar Typhi - Dufresne, Karine; Saulnier-Bellemare, Julie; Daigle, France (Frontiers in Cellular and Infection Microbiology, 2018)
The human-specific pathogen Salmonella enterica serovar Typhi causes typhoid, a major public health issue in developing countries. Several aspects of its pathogenesis are still poorly understood. S. Typhi possesses 14 fimbrial gene clusters including 12 chaperone-usher fimbriae (stg, sth, bcf, fim, saf, sef, sta, stb, stc, std, ste and tcf). These fimbriae are weakly expressed in laboratory conditions and only a few are actually characterized. In this study, expression of all S. Typhi chaperone-usher fimbriae and their potential roles in pathogenesis such as interaction with host cells, motility or biofilm formation were assessed. All S. Typhi fimbriae were better expressed in minimal broth. Each system was overexpressed and only the fimbrial gene clusters without pseudogenes demonstrated a putative major subunits of about 17 kDa on SDS-PAGE. Six of these (Fim, Saf, Sta, Stb, Std and Tcf) also show extracellular structure by electron microscopy. The impact of fimbrial deletion in a wild-type strain or addition of each individual fimbrial system to an S. Typhi afimbrial strain were tested for interactions with host cells, biofilm formation and motility. Several fimbriae modified bacterial interactions with human cells (THP-1 and INT-407) and biofilm formation. However, only Fim fimbriae had a deleterious effect on motility when overexpressed. Overall, chaperone-usher fimbriae seem to be an important part of the balance between the different steps (motility, adhesion, host invasion and persistence) of S. Typhi pathogenesis.